A Novel Lamé Mode RF-MEMS resonator with high quality factor. (15th August 2021) - Chen, Zeji; Wang, Tianyun; Jia, Qianqian; Yang, Jinling; Yuan, Quan; Zhu, Yinfang; Yang, Fuhua
Highlights: The bias voltage of this novel Lamé mode resonator is only 1.5 V, which is the lowest among the reported Lamé mode resonators. The proposed resonator implements a promising f × Q product up to 6.60 × 10 12, which is the highest among the state-of-art perforated Lamé mode resonators. The different loss sources of the proposed resonators were comprehensively analyzed to provide an insight into the loss mechanisms of the devices. Strategies can be accordingly taken to improve the Q values. A simple and reliable process was exploited to batch fabricate the high-performance resonators with nanoscale spacing gaps. The nonlinearity of the resonator was characterized to provide a guidance on stable operations of the device. Abstract: This work presents a high-performance Lamé mode resonator with high Q values. The anchor loss and thermoelastic damping (TED) were effectively decreased with the optimized tether design and etch hole distribution. A simple and reliable process was developed to batch fabricate the Lamé mode resonators with nano-scale spacing gap. In air, a low bias voltage of 2.5 V can excite a resonance peak height over 26 dB for the resonator with high Q of 8900. In vacuum, the required bias voltage was further down to 1.5 V, which is the lowest one among the reported Lamé mode resonators. A boosted Q value of 128400 was obtained, corresponding to the highest f × Q product of 6.60 × 10 12 among the state-of-art perforated ones. Moreover, the nonlinearities were experimentally observed, which provides helpful guidance on the stable operation of the resonators. The proposed resonator could have potential in building up advanced wireless communication systems with low power consumption and high-level integration. Graphical abstracts: Image, graphical abstract